Is it possible a processual ontology of biochemical entities? Considerations on the case of cell receptors and cell signaling - Alassia, Fiorela (Estudios de Filosofía, 2022)
Biological macromolecules, considered as the items of the biochemical domain, are typically conceived under the ontological category of substantial individuals. In this paper, I will argue that the philosophical framework of process ontology, according to which the living world is not populated by individuals but by a dynamic hierarchy of processes, is more adequate to account for the structure and functioning of macromolecules. In particular, I will analyze its application to the phenomenon of cell signaling and to one of its key concepts, cell receptors. Current knowledge in biochemistry allows us to conceive receptors as processual and dynamic entities, relationally stabilized and not separated from the biochemical phenomenon of which they are part.